Relaxation time mapping in multiple sclerosis. (March 2011) - Ropele, Stefan; Langkammer, Christian; Enzinger, Christian; Fuchs, Siegrid; Fazekas, Franz
Several relaxation mapping techniques have been proposed to quantitatively assess disease-related brain tissue changes in multiple sclerosis. Newer developments also account for the distribution of hydrogen protons in different tissue compartments, and therefore provide markers for myelin and macromolecular content. This article will cover the broad spectrum of the pulse sequences and analysis techniques related to this topic that are currently available. Various technical and practical limitations linked with specific approaches will be discussed. These include acquisition time, accuracy and precision, radiofrequency absorption and limited coverage of the brain. Finally, the application of these techniques in the context of multiple sclerosis will be reviewed.